Responding to Disaster-Related Loss and Grief: Recovering From the 2013 Flood in Southern Alberta, Canada. Issue 2 (17th February 2018) - Fulton, Amy E.; Drolet, Julie
ABSTRACT: Applying a loss and grief perspective, this article explores lived experiences and perceptions of social workers and human service professionals who provided psychosocial supports and services to children, youth, and families recovering from the 2013 flood in southern Alberta, Canada. Five interrelated themes emerged from the analysis: (a) challenges with providing services while experiencing personal loss; (b) lack of funding for long-term postdisaster psychosocial recovery; (c) parenting in the context of disaster-related loss; (d) children's and youth's experiences of disaster-related loss and grief; and (e) the impact of the flood on family socioeconomic status. Recommendations for research, education and practice are discussed.